Handling medical negligence: necessity of a proper system - Subedi, Nuwadatta (Journal of College of Medical Sciences-Nepal, 2017)
The issue of medical negligence has been catching attention of many people nowadays. With advancement of technology in medical field, many incurable diseases of past time can now be managed well at the cost of burdening expenditure. This has resulted in obvious expectations to the patient and their families that any ailment can be cured from the medical procedures and therapies. When these expectations are not met in terms of complications or death of the near ones, people get frustrated and tend to allege health care providers against medically negligent. Negligence are of two types; civil negligence where the doctors are alleged to have lost simple degree of care and attention to the patients thereby causing damage whereas in criminal negligence, the doctors grossly deviate from the standard of care and competence or perform activities which are understood prima facie as a crime, for eg: performing criminal abortion, organ transplantation against the law etc. Whatever the type of negligence, there are legal measures to file complaint against the doctors who are alleged to have caused negligence. Gone are the days when people regarded doctors near to gods. Medical service also falls under the consumer protection act where the patients are the consumers and medical personnel, the service providers. The patients have rights to get quality medical service under this act. If the patients or their relatives are dissatisfied with the medical service rendered to them by the health care providers, they have the right to lodge complaint to the compensation committee of the district in which chief district officer (CDO) is the chairman in each district. If there is an issue of criminal negligence, the complaint can also be filed in the concerned court. In some circumstances, when the patient develops complications or dies, the attendants accuse the doctors for the failure in treatment and protest in the hospital premises rather than opting the legal way of charging them against negligence. The health professionals are at times threatened and forced to apologize in public. Most of the times, they demand for compensation and many direct benefits to the relatives of the deceased. The hospitals and the health professionals feel insecure and often they have agreed to the demands put forth to peacefully settle the issue and to get prevented from defamation. The government is also unable to provide security. Similar cases have been reported time and again in Nepal, creating a sense of lawlessness in the country. When deciding whether a doctor is held liable for negligence, the “standard of care” should be analysed. It means the practice should be an accepted one and standard, such that doctor of the similar filed and competence would have also opted the same procedure in given circumstances. Even when a doctor has duly acted opting standard procedure, still there can be chances that a patient can develop complications. Every human body cannot react exactly same to a medical intervention though that may be a scientifically proven one as there can be chances of medical misadventure. The doctors should have possessed reasonable degree of care and skill when he is attending the patient. According to Bolam’s test, a person is said to have inappropriate standard, and becomes negligent, if it is proven that he had failed to do what a reasonable person would do in the circumstances.1 The degree of care and skill should be comparable to an average doctor in similar settings. In order to analyse these issues, expert opinion from reputable and unbiased experts of the similar field of medicine should be taken. In case of death due to alleged medical negligence, the dead body should be autopsied by qualified experts in Forensic Medicine. This can explain so many facts about the deceased which can be helpful to decide whether negligence has factually taken. It highlights the need of taking opinion from the experts of the concerned field by the councils framed to settle the cases of medical negligence, especially the consumer protection council, Nepal Medical Council, etc. It is a high time for the government to play role to address to this sensitive and quai-legal issue. If this trend is not ended, the trust of patients towards the doctors may nullify. The doctors also cannot work effectively when there is no safe working environment and may begin to have tendency to abandon handling critical cases with a fear of vulnerability to defamation if not physical assault in worst case. The situation is ultimately disastrous to the entire health care system. The very sensitive issue of health care delivery cannot be compared to any other commercial issues. The proper mechanism of addressing the issue of medical negligence should be practiced alongside encouragement from governmental urge to come up with better medicolegal systems in this regard. This is highly essential for balancing expectations of the patients and performance of medical professionals.